MapReduce a comprehensive review - Al-Khasawneh, Mahmoud Ahmad; Shamsuddin, Siti Mariyam; Hasan, Shafaatunnur; Abubakar Ibrahim, Adamu (Institute of Electrical and Electronics Engineers Inc., 2018)
MapReduce encompasses a framework in the processing and management of large scale datasets within a distributed cluster. The framework has been employed in several applications including search indexes generation, analysis of access log, document clustering, and other data analytics. A flexible computation model is adopted in MapReduce in addition to plain interface which comprises the functions of map and reduce. The interface is customizable based on application developers. MapReduce has captured the interest among many scholars whereby the interest has been on increasing its usability and efficiency in support to database-centric operations. Accordingly, this paper provides a complete review regarding a vast continuum of proposals and systems concentrating basically on the support of distributed data management and processing with the use of the framework of MapReduce.